Analis Aspek Pemasaran Pada Toko Online Keripik Kentang Batu di Desa Labuhan Kec. Sreseh Kab. Sampang Dalam Perspektif Studi Kelayakan Bisnis - Solihin, Raudlatus; Rohman, Abdur (Universitas 17 Agustus 1945 Semarang, 2024)
This research aims to analyze the marketing aspects of the online rock potato chips shop in Labuhan Village from the perspective of a business feasibility study. This analysis includes market segmentation, target market, marketing strategy, and sales projections. The research method used is a literature study with a qualitative approach. Data was collected through observation, interviews and literature study. The research results show that the main market segments for rock potato cracker products are local communities and domestic tourists. The target market consists of consumers from various age groups and socio-economic status. The recommended marketing strategy is online marketing, utilizing social media and local promotions. Sales projections in the medium term are quite promising with stable growth. This research contributes to the feasibility study of the rock potato chips business in Labuhan Village and can be used as a basis for making investment decisions and further business development.